Busines Feasibility Analysis Of Sri Rasa Crackers Factory In Bengkulu City - Maya Roma; Sulisti Afriani; Herlin Herlin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Feasibility studies are very important for Sri Rasa Cracker Factory Businesses that plan to expand their business with maximum profit that has been undertaken.  This study aims to analyze and determine the cost of revenue, profit, and business feasibility of the Sri Rasa Crackers Factory in Bengkulu City. The analysis method used to determine the feasibility of a business or investment based on legal aspects, market and marketing aspects, technological aspects, environmental aspects, and financial aspects using the Payback Period (PP) method, Net Present Value (NPV), Internal Rate Of Return (IRR), Profitability Index (PI), and Avarage Rate Of Return (ARR). The results of this study indicate that the feasibility test from the legal aspects, market and marketing aspects, technological aspects, and environmental aspects of the Sri Rasa Crackers Factory Business is feasible to run. From the financial aspect with the Payback Period (PP) method is 4.25 months Payback Period is now smaller than the economic life of 3 years, then the Sri Rasa Cracker Factory Business is feasible to develop. From the Net Present Value (NPV), the Sri Rasa Cracker Factory business is feasible to run because it gets a positive value, namely (Rp.485,589,698.8). From the Internal Rate of Return (IRR), the Sri Rasa Cracker Factory business is feasible to run because it has obtained a yield greater (22%> 20%) than the loan interest. From the Profitability Index (PI), the Sri Rasa Cracker Factory business obtained a result of 8.35, so it is feasible to develop. From the Avarage Rate Of Return (ARR), the Sri Rasa Cracker Factory business is feasible to run, because it gets a result of 8.35%.